Empirical Evidence from the Indonesian Stock Exchange: The Impact of Dividend Policy Decisions on Sharia Share Prices - Abdul Kadir MS; Burhannudin Burhannudin; Khuzaini Khuzaini; Bustani Bustani (Ilomata International Journal of Tax and Accounting, 2021)
This paper aims to obtain empirical evidence of the impact of dividend policy decisions on sharia share prices. An exploratory investigation on 26 selected firms listed on the Indonesia Stock Exchange's Jakarta Islamic Index with the criteria of reporting complete financial statements for the 2014-2018 period. The secondary data were examined with 130 data and then processed using SPSS 23 packages, which were then included in the analysis using standard regression. The investigation's findings provide empirical evidence that dividend policy decisions have a significant effect on sharia share prices. This study provides a theoretical contribution to a limited study that explores dividend policy with Islamic share prices in the context of the stock exchange. In practice, this research provides significant insight regarding the dividend policy that the company decides to increase the effectiveness of financial management in the context of a company that is considered to have sharia shares on the stock exchange, considering that the company's business success can increase the economic growth of a country.